Collaborative Governance Analysis in Reducing Marriage Dispensation Requests: A Study of Multi Layered Verification Mechanisms in Bondowoso Regency - Raudhatul Adhawiyah Novita Zaini; Lilik Wahyuni; Alifiulahtin Utaminingsih (Bulletin of Community Engagement, 2026)
This study examines the implementation of collaborative governance to reduce marriage dispensation requests in Bondowoso Regency, East Java, through a multi-layered verification mechanism involving six key stakeholders: Social Affairs Agency (Dinas Sosial P3AKB), Health Agency, Religious Court, Ministry of Religious Affairs, Children’s Forum, and community leaders. Utilizing the Ansell and Gash (2008) collaborative governance framework, this qualitative case study employs Miles and Huberman’s interactive model for data analysis. Findings reveal that formal collaboration through the 2023 Memorandum of Understanding and Cooperation Agreement, combined with a five‑stage verification innovation (digital filtering, mandatory psychological assessment, medical examination at five specialized referral health centers, cognitive filter, and a two‑year anti‑divorce stamped statement), successfully reduced dispensation requests by 87.6 percent, from 1,077 cases in 2020 to 133 in 2025. However, the persistence of unregistered marriages (37 percent of applicants) and pre‑marital pregnancy (25 percent) indicates a displacement effect, suggesting that procedural rigidity in formal mechanisms redirects behavior toward informal practices. The study proposes two norm transformation strategies: victim testimony‑based campaigns and religious authority legitimation. This research contributes to collaborative governance literature by identifying structural interdependence and layered institutional design as critical mechanisms for addressing socially rooted problems beyond voluntary compliance.